2017
DOI: 10.1024/0301-1526/a000655
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of monthly variation in occurrence of abdominal aortic aneurysm rupture

Abstract: Summary:Background: We performed a meta-analysis to assess the presence of an annual rhythmic variability of ruptured abdominal aortic aneurysm (RAAA) onset. Patients and methods: Eligible studies were observational studies enrolling patients with RAAA and reporting monthly incidence of RAAA. Study-specifi c estimates, i. e. monthly incidence of RAAA, were combined using the random-effects model. Chronobiological analysis was performed by applying a partial Fourier series to pooled monthly incidence by using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 23 publications
3
18
0
1
Order By: Relevance
“…Takagi and associates conducted an analysis of more than 14 studies including over 3,978 patients with rAAA and came to a similar conclusion like we did in this study: the seasons with the highest number of rAAA are autumn and winter, accounting for 18.01% of rAAA in October, 10.81% in December, and 9.00% of rAAA in January [11]. The reason why the incidence of rAAA is highest in autumn and winter is the fact that people spend more time indoors, when they are exposed to nicotinism, which again significantly affects the potential occurrence of rAAA [12].…”
Section: Discussionsupporting
confidence: 81%
“…Takagi and associates conducted an analysis of more than 14 studies including over 3,978 patients with rAAA and came to a similar conclusion like we did in this study: the seasons with the highest number of rAAA are autumn and winter, accounting for 18.01% of rAAA in October, 10.81% in December, and 9.00% of rAAA in January [11]. The reason why the incidence of rAAA is highest in autumn and winter is the fact that people spend more time indoors, when they are exposed to nicotinism, which again significantly affects the potential occurrence of rAAA [12].…”
Section: Discussionsupporting
confidence: 81%
“…From several studies, it appears that post operative need for pacemaker implantation is similar in both techniques, TAVI seems to have lower transvalvular gradients but more common peri-prosthetic leaks and, in the end, RD-AVR seems to have lower mortality rates [25] . Finally, a large study from D'onofrio et al [26] obseverd 2,177 patients (1,885 TAVI vs. 292 RD-AVR): they found similar incidence of 30-day and 1 year mortality rates, stroke, bleeding and myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Also a previous work of our group showed a similar survival after transcatheter or SAVR [13] . Takagi et al [14] analyzed 8 studies comparing SAVR and TAVI in 4244 patients from 2010 and 2015 and compared results in terms of gained left ventricular ejection fraction (LVEF) and left ventricular mass (LVM). This meta-analysis suggests greater LVM improvement after AVR, which may be due to higher incidence moderate aortic regurgitation after TAVI.…”
Section: Discussionmentioning
confidence: 99%
“…6 A recent meta-analysis showed that invitation to AAA screening in 64-year-old men significantly reduced both all-cause and AAA-related mortality. 7 The Society for Vascular Surgery (SVS) has recommended onetime duplex scan screening for AAAs in men aged 55 years or older with a family history of AAA, all men aged 65 years or older, and women aged 65 years or older who have smoked or have a family history of AAA. 8 In the United States, Medicare covers 1 ultrasound scan screening of men aged 65 to 75 years who ever smoked in their lifetime or men and women who have a family history of AAA disease as part of a "Welcome to Medicare" package.…”
mentioning
confidence: 99%